Everyday life in breast cancer survivors experiencing challenges: A qualitative study. (4th July 2018) - Jakobsen, Klara; Magnus, Eva; Lundgren, Steinar; Reidunsdatter, Randi J.
Abstract: Background: Early diagnosis and treatment of breast cancer results in an increasing number of survivors, some of whom face new challenges in their transition to daily life. Aim: Based on these experiences, the aim of this study was to describe the everyday life in breast cancer survivors experiencing challenges. Material and method: Eleven women recruited from a follow-up study of breast cancer patients participated in qualitative interviews about their everyday occupations seven years after ending treatment. The inductive analysis revealed ten categories that were organized into five subthemes under the two main themes 'bodily and mental loneliness' and 'new center of gravity in everyday life'. Results: Findings showed how relevant information and guidance; active support to the client and their relatives; and a balance between occupations at home and at work were important matters to handle their everyday life challenges. Conclusion and significance: By assisting these women in finding new patterns of meaningful occupations that positively affect their everyday life, the study suggests some central elements to be included in future follow-up practice for breast cancer survivors. Approaching this goal, occupational therapists should contribute to more involvement assisting cancer survivors and their partners in finding new patterns of meaningful occupations that positively affect their everyday life.